Rapid fabrication of detachable three‐dimensional tissues by layering of cell sheets with heating centrifuge. (31st January 2018) - Haraguchi, Yuji; Kagawa, Yuki; Hasegawa, Akiyuki; Kubo, Hirotsugu; Shimizu, Tatsuya
Abstract : Confluent cultured cells on a temperature‐responsive culture dish can be harvested as an intact cell sheet by decreasing temperature below 32°C. A three‐dimensional (3‐D) tissue can be fabricated by the layering of cell sheets. A resulting 3‐D multilayered cell sheet‐tissue on a temperature‐responsive culture dish can be also harvested without any damage by only temperature decreasing. For shortening the fabrication time of the 3‐D multilayered constructs, we attempted to layer cell sheets on a temperature‐responsive culture dish with centrifugation. However, when a cell sheet was attached to the culture surface with a conventional centrifuge at 22‐23°C, the cell sheet hardly adhere to the surface due to its noncell adhesiveness. Therefore, in this study, we have developed a heating centrifuge. In centrifugation (55 g ) at 36‐37°C, the cell sheet adhered tightly within 5 min to the dish without significant cell damage. Additionally, centrifugation accelerated the cell sheet‐layering process. The heating centrifugation shortened the fabrication time by one‐fifth compared to a multilayer tissue fabrication without centrifugation. Furthermore, the multilayered constructs were finally detached from the dishes by decreasing temperature. This rapid tissue‐fabrication method will be used as a valuable tool in the field of tissue engineering and regenerative therapy. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:692–701, 2018